2014
DOI: 10.1007/s00167-014-3385-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between patellar cartilage defects and patellofemoral geometry: a matched-pair MRI comparison of patients with and without isolated patellar cartilage defects

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 44 publications
6
119
4
1
Order By: Relevance
“…A significant relationship between cartilage lesions and trochlea dysplasia has been documented. [33][34][35] In a 50-month follow-up of 46 patients after trochleoplasty, Neumann et al observed, , that in a subgroup of 26 patients with radiographic degenerative changes or intraoperative findings of chondromalacia there were comparable subjective postoperative improvements in this group, compared with the patients without chondral changes. Based on these results, it seems reasonable to include patients with more degenerative cartilage changes in the trochlea as an indication for ADT.…”
Section: Discussionmentioning
confidence: 87%
“…A significant relationship between cartilage lesions and trochlea dysplasia has been documented. [33][34][35] In a 50-month follow-up of 46 patients after trochleoplasty, Neumann et al observed, , that in a subgroup of 26 patients with radiographic degenerative changes or intraoperative findings of chondromalacia there were comparable subjective postoperative improvements in this group, compared with the patients without chondral changes. Based on these results, it seems reasonable to include patients with more degenerative cartilage changes in the trochlea as an indication for ADT.…”
Section: Discussionmentioning
confidence: 87%
“…For the trochlear measurements (SA, TD, facet asymmetry and LTIA), 14 studies were excluded from at least one of the measurements for using osseous landmarks or due to the lack of a clear description of measurement parameters reported 3 7 9 11 12 29 30 32 34 35 38–41…”
Section: Methodsmentioning
confidence: 99%
“…All of the control data were from patients with knee symptoms other than PF; for example, meniscal, cartilage and/or ligamentous injuries 6 9–12 15 17 30 37 38 42–44. Only two papers used a strict definition of normals (asymptomatic volunteers) 41 45.…”
Section: Methodsmentioning
confidence: 99%
“…Eine aktuelle Studie zeigte, dass behandlungsbedürftige retropatellare Knorpelschäden auch in diesen Fällen zu fast 90 % mit Begleitpathologien wie einer Trochleadysplasie, einem Patellahochstand (Patella alta) oder andersartigen geometrischen Formveränderungen des patellofemoralen Gelenkabschnitts assoziiert sind [4]. Der Knorpelschaden sollte in diesen Fällen als Epiphäno-men der zugrunde liegenden Pathologie, die zu einem Malalignment oder auch ohne Luxationsereignisse zu einer patellofemoralen Instabilität führen kann, erkannt, interpretiert und entsprechend behandelt werden.…”
Section: » Knorpelschäden Sind Zu Etwa 90 % Mit Begleitpathologien Asunclassified